Need for Reliability Assessment of Parent Product before Redesigning a New Product - Faiz, Mohd Turan; Aikhuele, Daniel Osezua (Indian Academy of Sciences, 2017)
As companies increasingly invest on the development of new products, and in the redesigning of existing ones in order to meet the ever emerging and rapidly changing customer demands, they continue to face an extremely competitive and cost-cutting war. Since today’s product design works are mainly focused on the redesigning of existing products, most especially for complex products and systems, their properties are expected to be of higher technical content, reliability requirements as well as design characteristics.